Shrinkage Differential of Wood as a Tool to Monitor Drying Stresses - Kumar, Shailendra; Kandpal, R. P.; Ramkishore (Indian Forester, 2015)
The shrinkage pattern of wood provides some important information to monitor the drying stresses. Knowledge of timing, severity and reversal of the drying stresses may help to develop faster kiln drying schedules. Tangential shrinkage at core and shell layers of wood was measured in intact condition and slices were cut from exactly same layers. The slices were allowed to relieve their stresses first and then oven dried. The results indicate that shell layers of the wood are affected by higher magnitude of the drying stresses as compared to core layers. The results also indicate that after the stress reversal in wood, the rate of tangential shrinkage of wood also changes. In 41 days of drying, the stress reversal and shift in rate of intact shrinkage of wood in tangential direction coincided on day 21 of the drying. This work demonstrates that it is possible to determine the timing of the stress reversal by monitoring the rate of the change of wood shrinkage in tangential direction.